Le genre féerique illustré à l’époque victorienne : splendeurs et déclin d’un genre entré en résistance - Audrey Doussot (Cahiers Victoriens et Edouardiens)
After having been blacklisted for decades, fairy tales unexpectedly came back into favour in Great Britain during the Victorian period, being staunchly supported by authors like Ruskin, Dickens or MacDonald. Visual arts too drew inspiration from fairy literature and lore, appropriating their themes, motifs and characters. In this context, illustrated Victorian fairy tales became vehicles of resistance against the banishment of imaginary supernatural literature and the rejection of illustration as art. But the vocation of fairy tales being, according to Jack Zipes, to interact with society, they also conveyed social resistance (against rising capitalism, growing materialism or stifling gender roles) as De Morgan’s or Housman’s tales testify. The Victorian period was a phase of triumph for fairy literature before its fighting spirit was smothered by a tendency to conform to middle-class normative ideology and an increasingly infantilized content.